Agricultural producers and their markets - Warley, T. K.; Great Britain (New York: Kelley, 1967)
This book is a collection of papers read at an international seminar sponsored by the Ministry of Overseas Development. Held at the University of Nottingham.
Bibliographical footnotes.
usc 29/01/2019
Loans
Keywords: Farm produce; Produce trade; Cooperative marketing of farm produce